Educational quality management model for the francisco de paula santander university ocaña section under the NTC ISO 21001: 2019 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Quality in educational institutions has become a fundamental pillar that seeks that said organizations can comply with each of the applicable regulatory requirements, but also with the requirements of their interested parties.  The objective of this article is to compile the concepts and studies carried out around the quality management systems implemented in higher education institutions, their contribution to the quality assurance processes that seek institutional accreditation and how these institutions can apply the NTC. ISO 21001 in the search for quality standards in educational organizations that guarantee the provision of relevant, socially responsible, personalized educational service, among other benefits, thus increasing the satisfaction of its interested parties.  The results of the studies analyzed demonstrate the convenience and advantages of having a quality management system for educational organizations aligned with the policies of an institution and the articulated work with the other models and implemented systems focused on strengthening the strategies that promote a management effective education.
Keywords: Quality; Quality in education; ISO 21001; management system; higher education